IMPLEMENTASI KEBIJAKAN PENGELOLAAN ARSIP DI KANTOR CAMAT JIRAK JAYA KABUPATEN MUSI BANYUASIN - juliartha, Edwar; Yuslainiwati, Yuslainiwati; Budiman, Arief; Pereira, Julio; Verawati, Linda (MAP Program Pascasarjana Universitas Sjakhyakirti, 2024)
The aim of this research is to find out how the archive management policy is implemented at the Jirak Jaya District Office, Musi Banyuasin Regency. The research method used is qualitative. The focus of this research is on the Implementation of Records Management Policy with several elements that must be implemented through 1) Communication, 2) Resources, 3) Disposition 4) Bureaucratic Structure. This research data comes from primary data and secondary data. The data collection procedures for this research are 1) Stages of entering the field (getting in), 2) Stages of being in the field (getting along), 3) Stages of leaving the field (getting out). Based on the research results, it can be concluded that in 1) communication there are different sources of information and it is not clear in conveying information that details about static archive management have not been included in the RENSTRA and RENJA and have not been conveyed optimally to interested parties regarding the basic documents that become policies. static archive management; 2) Resources, there has not been a master plan related to the provision of static archive management facilities, instead what has happened is a partial plan which has a tendency to be patchy in meeting the needs of these facilities, and there is no functional archivist who has special archive management capabilities; 3) Disposition, the attitude of data and information management officers towards static records management policies is still not good, because formally static records management policies are still a new category of affairs within the scope of regional government bureaucracy; 4) Bureaucratic structure, there is overlapping division of authority in the Data and Information Management Section of the Jirak Jaya Subdistrict Office, Musi Banyuasin Regency.